DEVELOPMENT OF DOMESTIC TOURISM IN THE MIDST OF MODERN CHALLENGES: ANALYSIS OF INTERNATIONAL EXPERIENCE AND PROSPECTS FOR UKRAINE DURING THE WAR AND POST-WAR RECOVERY - PANKIV, Natalia; MELNYK, Solomiya (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is dedicated to a comprehensive analysis of domestic tourism in Ukraine under martial law and during the period of post-war recovery. It highlights the key trends and transformations in the domestic tourism sector that have emerged under the influence of the full-scale war, showing how the industry has adapted to new realities. Among the main issues identified are travel safety concerns related to the constant threat of missile strikes and air raids, the urgent need to adapt tourist facilities to new security and logistical conditions, a decline in the population’s purchasing power due to economic instability, and the general challenges in ensuring stable development of tourism infrastructure and services. The study emphasizes that the war has acted as a catalyst for the redistribution of tourist flows within the country: the popularity of Western Ukrainian regions, such as the Carpathians and Transcarpathia, has significantly increased as they provide a relatively safe environment, picturesque landscapes, and a well-developed tourist infrastructure that can accommodate both temporary displaced persons and traditional travelers.Particular attention is devoted to the emergence and growing significance of new forms of tourism, including volunteer tourism, military tourism, and memorial tourism, which reflect the realities of life under martial law and the population’s efforts to combine leisure with civic engagement and commemoration. The article also examines international experiences in overcoming the consequences of armed conflicts in the tourism sector, focusing on successful recovery strategies applied in Israel, Croatia, and Bosnia and Herzegovina. These international cases serve as an important comparative basis for adapting effective approaches to the Ukrainian context, particularly in terms of rebuilding infrastructure, restoring trust in safety, and promoting destinations through innovative marketing tools. The research concludes that the most critical factors for successful post-war recovery of domestic tourism in Ukraine include targeted infrastructure investment, systematic support for local community initiatives, preservation and promotion of cultural and historical heritage, development of sustainable and eco-friendly forms of tourism, as well as the active use of digital technologies and online platforms for marketing and promotion of domestic tourism products. Based on the findings, the article formulates a set of practical recommendations aimed at stimulating and supporting the development of domestic tourism in Ukraine, which in turn may serve as a driver of regional economic recovery, social cohesion, and long-term resilience.
Keywords: tourism; war; Ukraine; international experience; post-war recovery